A central circadian oscillator confers defense heterosis in hybrids without growth vigor costs - Li Yang (Nature Portfolio, 2021)
There is frequently a trade-off between plant immunity and growth. Here the authors show that the epigenetic control of CCA1, encoding a core component of the circadian oscillator, simultaneously promotes heterosis for both defense and growth in hybrids under pathogen invasion.